Estudo taxonômico das espécies da família Cucurbitaceae Juss. ocorrentes no Distrito Federal, Brasil - Leal, Iada Anderson Barbosa (2013)
Taxonomical study of species from the family Cucurbitaceae Juss. that occur on the Federal District (Distrito Federal), Brazil – The Cucurbitaceae Juss. family is numerous and widespread in its respective taxa, however, with conflicting data about the exact numbers regarding them. The present work is a survey of plants of this family found in the Federal District, Brazil, with the scope of refining the accuracy of such data. With this intention, some analysis of exsicates deposited in national and international herbaria were made and some expeditions were done at the area of study. Seven genera and fourteen native species were found in the researched area, as well as five genera and five species cultivated or subespontaneus. Related to native plants, the genus Cayaponia Silva Manso presented a greater number os species (5), followed by Melothria L. (3) and Psiguria Neck ex Arn. (2), being the genera Gurania Cogn., Melothrianthus Mart. Crov.; Sicyos L. and Wilbrandia Silva Manso are represented by only one specie for each one of those. Considering only the material deposited in herbaria, five species were found cultivated or subespontaneous: Cucumis dipsaceus Ehrenb., Cucurbita maxima Duch., Lagenaria siceraria (Molina) Standl., Luffa cylindrica M. Roem. and Momordica charantia L.